Endoscopy-assisted extraction of penetrating a wayer arrow in the ethmoid sinus - Nayoan, Christin Rony; Lopo, Christian; Lopo, Wigia Hanalia; Rahma, Rahma; White, IPFI (Oto Rhino Laryngologica Indonesiana, 2025)
Background: Using wayer arrows in attack activities carried out by a person, or a group of people is rife in Palu. Arrow injuries are classified as low velocity, but can be significantly life-threatening when the vital organs are affected. Endoscope-assisted surgery is one of the techniques of penetrating sinus injury management. Purpose: To describe the management of a unique case in otorhinolaryngology field. Case report: A 21-years old male patient was diagnosed with penetrating ethmoid sinus trauma caused by a wayer arrow. Extraction was performed to release the arrow using an endoscope. Clinical question: What kind of foreign bodies can penetrate into the paranasal sinuses? Is endoscope-based surgery approach, the correct technique for penetrating sinus injury management? Method: A literature search was performed on Pubmed and Google scholar using keywords “foreign body”, AND “sinus surgery”, AND “wayer arrow”. Result: The search obtained 19 articles, including 4 reports of wayer arrow penetrating paranasal sinus. Conclusion: The use of endoscopy for ethmoid sinus penetrating trauma gives good results.